An empirical analysis of the impact of income inequality and social capital on physical and mental health - take China's micro-database analysis as an example - Yuanyuan He; Lulin Zhou; Junshan Li; Jun Wu (BMC, 2021)
Abstract Background Income inequality is one of the important reflections of the unbalanced development of the world economy and can have adverse effects on physical and mental health. Methods This article used the 2018 China Family Panel Studies Database as an empirical analysis data source. The Kakwani index (KI) was used to measure income inequality, and social capital was broken into cognitive social capital and structural social capital. Our assessment was conducted by using STATA16 software for ordered logistic regression, verifying income inequality, social capital on correlation between physical and mental health firstly; then by gradual regression methods to verify intermediary effect, and demonstrate the social capital as an intermediary variable affecting physical and mental health as income inequality. Result The income inequality has a significant negative effect on physical and mental health (β = − 0.964, − 0.381; OR = 0.382, 0.758; P < 0.01), Social capital has a significant effect on physical and mental health (Cognitive SC(MH): β = 0.146 and 0.104, OR = 1.157 and 1.110, P < 0.01; Cognitive SC(PH): β = 0.046 and 0.069, OR = 1.047 and 1.071, P < 0.01; Structural SC(MH): β = − 0.005, 0.025 and 0.015, OR = 0.995, 1.025 and 1.015, P > 0.1, P < 0.01 and P < 0.01; Structural SC(PH): β = − 0.026, 0.009 and − 0.013, OR = 0.975, 1.009 and 0.987, P < 0.01, P > 0.1 and P < 0.01). Our analysis also showed that social capital (cognitive social capital and structural social capital) has an intermediary effect on physical and mental health due to income inequality. Conclusion This study shows that income inequality can not only directly affect physical and mental health, but also through social capital intermediary utility indirectly affect physical and mental health, social capital has positive effects on physical and mental health. At the same time, income inequality and social capital's effects on physical and mental health exist regional differences, urban-rural differences, and gender differences. Therefore, in the development of special policies to support and take care of vulnerable groups, special attention needs to be paid to poor rural areas and female groups.